Extensive Analysis of GmFTL and GmCOL Expression in Northern Soybean Cultivars in Field Conditions. - Guangyu Guo; Kun Xu; Xiaomei Zhang; Jinlong Zhu; Mingyang Lu; Fulu Chen; Linpo Liu; Zhang-Ying Xi; Andreas Bachmair; Qingshan Chen; Yong-Fu Fu (PLoS ONE)
The FLOWERING LOCUS T (FT) gene is a highly conserved florigen gene among flowering plants. Soybean genome encodes six homologs of FT, which display flowering activity in Arabidopsis thaliana. However, their contributions to flowering time in different soybean cultivars, especially in field conditions, are unclear. We employed six soybean cultivars with different maturities to extensively investigate expression patterns of GmFTLs (Glycine max FT-like) and GmCOLs (Glycine max CO-like) in the field conditions. The results show that GmFTL3 is an FT homolog with the highest transcript abundance in soybean, but other GmFTLs may also contribute to flower induction with different extents, because they have more or less similar expression patterns in developmental-, leaf-, and circadian-specific modes. And four GmCOL genes (GmCOL1/2/5/13) may confer to the expression of GmFTL genes. Artificial manipulation of GmFTL expression by transgenic strategy (overexpression and RNAi) results in a distinct change in soybean flowering time, indicating that GmFTLs not only impact on the control of flowering time, but have potential applications in the manipulation of photoperiodic adaptation in soybean. Additionally, transgenic plants show that GmFTLs play a role in formation of the first flowers and in vegetative growth.